2023
DOI: 10.3171/case2387
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of sural nerve entrapment aided by imaging- and electrography-based diagnosis: illustrative case

Abstract: BACKGROUND The sural nerve (SN) is a cutaneous sensory nerve that innervates the posterolateral side of the distal third of the leg and lateral side of the foot. The SN has wide variation in its course and is fixed to the subcutaneous tissue and superficial fascia. Idiopathic spontaneous SN neuropathy is rarely surgically treated because of the difficulty in detecting SN entrapment. OBSERVATIONS Herein, the authors present a rare case of surgically treated spontaneous SN neuropathy. A 67-year-old male patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…TO THE EDITOR: We read with interest the article by Matsubara et al 1 who reported on a 67-year-old male diagnosed with right sural nerve entrapment at the level behind the right lateral malleolus, confirmed by magnetic resonance imaging (MRI) and sensory nerve conduction studies ( Matsubara M, Yagi K, Hemmi S, et al Surgical treatment of sural nerve entrapment aided by imaging- and electrography-based diagnosis: illustrative case. J Neurosurg Case Lessons .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TO THE EDITOR: We read with interest the article by Matsubara et al 1 who reported on a 67-year-old male diagnosed with right sural nerve entrapment at the level behind the right lateral malleolus, confirmed by magnetic resonance imaging (MRI) and sensory nerve conduction studies ( Matsubara M, Yagi K, Hemmi S, et al Surgical treatment of sural nerve entrapment aided by imaging- and electrography-based diagnosis: illustrative case. J Neurosurg Case Lessons .…”
mentioning
confidence: 99%
“…The patient underwent surgical neurolysis, which resulted in significant pain reduction over a follow-up period of 10 months. 1 The study is impressive but has limitations that should be discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation